Exploring regulatory network of icariin synthesis in Herba Epimedii through integrated omics analysis - Zhu, Xuedong; Wen, Shiqi; Gul, Hameed; Xu, Pan; Yang, Yang; Liao, Ximei; Ye, Yunling; Xu, Zijian; Zhang, Xiaofang; Wu, Lin (Frontiers in Plant Science, 2024)
Herba Epimedii's leaves are highly valued in traditional Chinese medicine for their substantial concentration of flavonoids, which play a crucial role in manifesting the plant's therapeutic properties. This study investigated the metabolomic, transcriptomic and proteomic profiles of leaves from two Herba Epimedii cultivars, Epipremnum. sagittatum (J) and Epipremnum. pubescens (R), at three different developmental stages. Metabolite identification and analysis revealed a total of 1,412 and 1,421 metabolites with known structures were found. Flavonoids made up of 33%, including 10 significant accumulated Icariinicariin analogues. Transcriptomic analysis unveiled totally 41,644 differentially expressed genes (DEGs) containing five encoded genes participated in icariin biosynthesis pathways. Totally, 9,745 differentially expressed proteins (DEPs) were found, including Cluster-47248.2.p1 (UDP-glucuronosy/UDPglucosyltransferase), Cluster-30441.2.p1 (O-glucosyltransferase), and Cluster-28344.9.p1 (anthocyanidin 3-O-glucoside 2 "-O-glucosyltransferase-like) through proteomics analysis which are involved to Icariinicariin biosynthesis. Protein-protein interaction (PPI) assay exhibited, totally 12 proteins showing a strong relationship of false discovery rate (FDR) <0.05) with these three proteins containing 2 leucine-rich repeat receptor kinase-like protein SRF7, and 5 methyl jasmonate esterase 1. Multi-omics connection networks uncovered 237 DEGs and 72 DEPs exhibited significant associations with the 10 Icariinicariin analogues. Overall, our integrated